“Tobacco has Blossomed like the Rose in the Desert”: Technology, Trees, and Tobacco in the Norfolk Sand Plain, c. 1920-1940 - McQuarrie, Jonathan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
Drawing on rural, biotechnological, and environmental history, this article examines how farmers, corporations, and the state deployed developments in silviculture and agriculture to reshape Norfolk County, Ontario. It traces the emergence of a relatively vibrant flue-cured tobacco sector during the Great Depression, a sector that both broke from and drew on earlier reforestation efforts that had emerged at the start of the twentieth century. In this context, tobacco and trees can best be viewed as biotechnologies connected to a continental flow, rather than simply as natural products. The article also argues that raising both trees and tobacco drew on ideas of conservation and resource management that were tightly bound to the development of rural capitalism, but highlights how the soil and environment influenced the capitalist objective of profitable rural development in ways that frustrated the idea of nature being manageable. It ends by noting that despite the ascendency of capitalist-informed ideas about rural development in Norfolk, other ways of understanding soil and the environment persisted.